Особенности языка памятников деловой письменности московской руси (на материале явочных челобитных XVII века) - Чащина, Е.А. (Investigationes Linguisticae, 2005)
The article presents the language structure of petitions of the 17th century and analyses structural and formal features of these documents. A special attention is given to the analyses of standardized documents included in the beginning and the end of the document (entitling, vassalage, petitioning formulas, etc.) The informative part includes the description of thrashings, robberies etc, and the formulas and collocations are also showed there up. But considerable attention is given to the analyses of the folk-and-spoken language elements the use of which results from the specific reasons including the conditions of the informative and psychological features, etc.